2020
DOI: 10.1186/s12885-020-07211-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple formin proteins participate in glioblastoma migration

Abstract: Background: The prognosis of glioblastoma remains poor, related to its diffuse spread within the brain. There is an ongoing search for molecular regulators of this particularly invasive behavior. One approach is to look for actin regulating proteins that might be targeted by future anti-cancer therapy. The formin family of proteins orchestrates rearrangement of the actin cytoskeleton in multiple cellular processes. Recently, the formin proteins mDia1 and mDia2 were shown to be expressed in glioblastoma in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…These results indicate that FMNL1 may have a role in GC tumor progression. A similar association has been seen in other cancers [8,27].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results indicate that FMNL1 may have a role in GC tumor progression. A similar association has been seen in other cancers [8,27].…”
Section: Discussionsupporting
confidence: 86%
“…We chose cell lines representing well differentiated (MKN28) and poorly differentiated (AGS, MKN45) GC. The cell stainings showed typical dot-like expression patterns and cytoplasmic location along the actin filaments, which have been previously reported in other cancer cell types [7,8,20]. This cytoplasmic pattern was recapitulated in the gastric cancer tissue samples, further confirming the integrity of the immunohistochemical stainings.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, considering this last point, and the fact that this is the first study indicating the correlation between the upregulated DAAM1 protein level and CS, it may be assumed that the involvement of this formin in the cellular events leading to neoplastic transformation. However, in this context, the role of other formins cannot to be excluded, since it has been previously demonstrated that the up-regulation of many of these family members, such as mDia, DIAPH1, and FMNL, has been positively correlated to cancer progression [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Therefore, the study of such proteins in CS may be of great interest, but it is beyond the scope of this paper, which is exclusively focused on DAAM1.…”
Section: Resultsmentioning
confidence: 99%
“… 15 Its effect could be synergistic with the mutation of the formin FHOD1, also involved in migration of glioma cells in vitro . 16 , 17 …”
Section: Discussionmentioning
confidence: 99%